Chinese-style pragmatic objectivity in war reporting - Zhang, Shixin Ivy (Taylor & Francis, 2015)
China plays an increasing role in the wars and conflicts around the world with its expanding political and economic interests overseas, and its diplomatic role in international affairs. More and more Chinese journalists go to the frontlines overseas to cover distant conflicts for domestic audiences. Based on semi-structured in-depth interviews with sixteen Chinese correspondents who have covered conflicts outside China, this study examines Chinese journalists’ perceptions and reflections on objectivity in the war zones. The author adopts a term of Chinese-style pragmatic objectivity to mean that objectivity is a convenient approach for Chinese journalists to do war journalism in the field. At the level of objectivity-as-a- value, objectivity is defined as a pragmatic value and a practical ritual for Chinese journalists to do news within the scope they can reach, to protect themselves from criticisms, and to justify their version of the truth. It promotes allegiance and patriotism. At the level of objectivity-as-a-practice, objectivity in war coverage is compromised by China’s foreign policies, military constraints, the press’s political orientations and editorial polices, and journalists’ personal experiences and values. Chinese journalists use Chinese-style objectivity to negotiate their roles in the power struggle with the state, foreign militaries, the newsroom and journalists.